2015
DOI: 10.11648/j.avs.s.2015030501.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Yeast (Saccharomyces cerevisiae) Supplementation on Performance, Carcass Characteristics and Some Metabolic Responses of Broilers

Abstract: Abstract:This study was conducted to evaluate the effect of feeding graded levels of yeast on broiler performance, carcass characteristics and some hematological indices. One day old Hubbard broiler chicks (n=160) were randomly allocated to five dietary treatments. Each treatment consisted of 4 replicates of 8 broilers each. The dietary treatments contained 0% yeast (Saccharomyces cerevisiae) as a negative control diet, 0% yeast + 30 ppm Oxytetracyline as a positive control, 1%, 2% and 3% yeast in the starter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(33 reference statements)
7
13
1
Order By: Relevance
“…Also, in another assay were noticed that addition of T (2.5-7.5 g/Kg food) findings, in these research, the addition of Sc alone, in the same level used on this experiment, did not modify productive variables (Rezaeipour et al, 2012). Coincidently to this results, in another research, was registered that broilers fed Sc in higher levels to use on this experience (1-3%) and noticed high Consumption but lower Weight Gain (Ahmed et al, 2015). Opposite to this results, we and another researcher noticed better Feed Conversion and increased Weight Gain in broilers fed Sc (0.1-0.75%) (Miazzo et al, 2001(Miazzo et al, , 2003Nilson et al, 2004;Geishari & Kholehipour, 2006;El Naga, 2012).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Also, in another assay were noticed that addition of T (2.5-7.5 g/Kg food) findings, in these research, the addition of Sc alone, in the same level used on this experiment, did not modify productive variables (Rezaeipour et al, 2012). Coincidently to this results, in another research, was registered that broilers fed Sc in higher levels to use on this experience (1-3%) and noticed high Consumption but lower Weight Gain (Ahmed et al, 2015). Opposite to this results, we and another researcher noticed better Feed Conversion and increased Weight Gain in broilers fed Sc (0.1-0.75%) (Miazzo et al, 2001(Miazzo et al, , 2003Nilson et al, 2004;Geishari & Kholehipour, 2006;El Naga, 2012).…”
Section: Resultssupporting
confidence: 70%
“…Perhaps, the different result must be attributed to the difference in Sc nature and T levels (30% vs 0.25-0.75 g/Kg feed) used in each assay. In another experience were register increased values in carcass performance in broilers fed Sc alone (0.1-1%) (Miazzo et al, 2007(Miazzo et al, , 2011Ahmed et al, 2015). significantly better in broiler received the combination of both additives in all T levels (Table 4 and Figure 2).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…A decrease in serum cholesterol and serum albumin with increasing dietary yeast levels in broiler diets was observed and no detrimental effects on the birds performance occurred up to an inclusion level of 1% (w/w) (Ahmed et al ) (Fig. ).…”
Section: Probiotic Yeast For Poultrymentioning
confidence: 98%
“…Carcass yield in Table 2 showed that Agaricus bisporus and Auricularia auricula crude extract addition in average 70.6 -73.5%, which is broiler carcass yield at about 70 -75%. In study of 3% yeast cell wall inclusion into broiler diets did not show significant differences compared with oxytetracycline group (Ahmed et al, 2015). Kavyani et al (2012) also reported that 3% Agaricus bisporus inclusion in broiler diet showed 73.3% carcass yield with no significant differences between treatments.…”
Section: Resultsmentioning
confidence: 90%